Discoveries, tolerance, pluralism, utopias - Hoyos Vásquez, Guillermo (Estudios de Filosofía, 2008)
We could say that pluralism is the affirmative face of tolerance and its ultimate justification. For this reason we return to the phenomenological description of the way the world is given to us. In the return to the origin of philosophy and science in Greece, phenomenology discovers that the original meaning of the world of life is essentially multicultural. Indeed, in a prescientific attitude the world is given in each culture from its own traditions, myths and customs. Each culture tends to identify its vision of the world with the one world: it becomes intolerant and tries to dominate other cultures.